Conceptual Framework for Strategic Entrepreneurship in Manufacturing SMEs in India - Tilekar, Girish (Global journal of Business and Integral Security, 2025)
Strategic entrepreneurship essentially can be considered as a creative combination of strategic management principles and entrepreneurship principles to achieve superior returns and generate wealth. Indian Manufacturing sector currently struggles to achieve and sustain superior performance under volatile and dynamic market conditions (VUCA conditions) Competition from Chinese manufacturing firms further threatens the very viability of many manufacturing firms in India. Strategic entrepreneurship construct and principles will greatly help such firms to navigate the VUCA conditions and compete successfully. Currently there is no specific implementable or guiding framework which management of manufacturing firms in India can adapt. This research intends an implementable guiding framework. Strategic entrepreneurship is still evolving as concept. Scholars continue to debate regarding its boundaries and dimensions. There are various concepts in literature to tackle dynamics in marketplace and business environments, creative practices in business administration, more recently digitalization strategy has become part of management practices. These theories concepts tools and methods are segregated in various domains. This research will creatively integrate this topic in context of strategic entrepreneurship. This is done first by performing extensive literature review in creativity, and how dynamic capability and digitalization of manufacturing systems are manifested and developed. A small survey of detail interview is conducted to understand the managerial competence with respect to strategic entrepreneurship elements in manufacturing SMEs. A new conceptual framework is developed and proposed with addition of new elements. With this element strategic entrepreneurship construct is made applicable to manufacturing SMEs.